2002
DOI: 10.1002/jrs.944
|View full text |Cite
|
Sign up to set email alerts
|

On far‐wing Raman profiles by CO2

Abstract: The anisotropic scattering spectrum of the symmetric stretching n 1 band by CO 2 was recorded up to the far Stokes wing, and its theoretical analysis was attempted through the non-Markovian energy-corrected sudden approximation -a useful approach which has thus far been successfully applied to the anisotropic scattering spectrum by N 2 , up to the far wing. Despite the excellent agreement observed in N 2 here, a substantial inconsistency between theory and experiment was found in the wing of the spectrum. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The non-Markovian ECS-BC method (assuming a structureless bath) works well for the N 2 -N 2 system because of the nearly isotropic interaction between two small N 2 molecules. In the case of longer and more anisotropic colliders like CO 2 , it gives underestimated intensities in the far wing, [18] so that the internal structure of the perturber should be accounted for, as it is done in the present spectral-moments approach.…”
mentioning
confidence: 95%
“…The non-Markovian ECS-BC method (assuming a structureless bath) works well for the N 2 -N 2 system because of the nearly isotropic interaction between two small N 2 molecules. In the case of longer and more anisotropic colliders like CO 2 , it gives underestimated intensities in the far wing, [18] so that the internal structure of the perturber should be accounted for, as it is done in the present spectral-moments approach.…”
mentioning
confidence: 95%
“…57,58 These studies indicate that there is a considerably deeper attractive minimum at short range in the OH(X)-O 2 potential than for OH(X)-N 2 . On the other hand, a number of related collisional experiments 19,[34][35][36][37]59,60 suggest larger cross-sections for N 2 than O 2 , which have conventionally been explained by stronger long-range interactions due to the larger N 2 quadrupole moment. We discover here which of these opposing factors might dominate in the combination of inelastic and elastic depolarisation processes sampled by the PS method.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of spontaneous Raman scattering studies have therefore been included in the special issues. Chrysos et al published a series of papers on collisioninduced scattering spectroscopy of carbon dioxide, [130,131] nitrogen, [130] and noble gases such as neon [132,133] and argon. [131,133,134] Schlüter et al demonstrated the application of a Raman gas analyzer for anesthesia monitoring.…”
Section: Spontaneous Raman Scattering Techniquesmentioning
confidence: 99%